2010
DOI: 10.1039/c0cp00217h
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes in the water tetramer. A combined Monte Carlo and DFT study

Abstract: The heat capacity curve of the water tetramer has been calculated at various levels of theory and over a broad range of temperatures, T = 50-200 K. Parallel-tempering and multiple-histogram Monte Carlo methods have been used and combined with the Density Functional Theory calculations of intra-cluster interactions via the Boltzmann-reweighting approach. It is demonstrated that such a combination can yield well converged thermodynamic data even for a modest number of sample configurations, which makes the metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…A new STM report by Jiang et al observed twodimensional ice on an Au(111) surface [15]. Also, we simulated the adsorption of water Vitek et al calculated the geometry structure of water tetramer [17]. Besides the four linked hydrogen bonds' inner four-molecule ring, the arrangement of the four dangling hydrogens is up-down-up-down with respect to the planar square cycle.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A new STM report by Jiang et al observed twodimensional ice on an Au(111) surface [15]. Also, we simulated the adsorption of water Vitek et al calculated the geometry structure of water tetramer [17]. Besides the four linked hydrogen bonds' inner four-molecule ring, the arrangement of the four dangling hydrogens is up-down-up-down with respect to the planar square cycle.…”
Section: Discussionmentioning
confidence: 94%
“…Vitek et al calculated the geometry structure of water tetramer [17]. Besides the four linked hydrogen bonds' inner four-molecule ring, the arrangement of the four dangling hydrogens is up-down-up-down with respect to the planar square cycle.…”
Section: Adsorption Of Water Tetramer On An Nacl(001) Surfacementioning
confidence: 99%
“…Both the temperatures and pressures have been spaced non-uniformly along the temperature or pressure axes. Following an earlier study, 19 the exponential increase of spacings is used for temperatures with the spacing between the two largest temperatures being 15 times larger than the spacing between the two lowest temperatures. For pressures, approximately exponential increase of spacings has also been used, but disturbed by adding a few additional pressures in the region where a phase change has been detected between lowpressure and high-pressure solid forms of [H 2 O] 15 and [H 2 O] 15 CH 4 (see Section 3).…”
Section: Methods and Computations 21 Simulationsmentioning
confidence: 99%
“…These problems are minimized with the use of extended ensemble techniques, such as parallel tempering Monte Carlo (PTMC), which uses several replicas at different temperatures to build a new ensemble where attempts to exchange between replicas at different temperatures are performed. Although PTMC methodology has been applied to study several atomic and molecular clusters [14][15][16][17][18][19][20][21][22][23][24][25] , to the best of our knowledge, its use with microsolvation systems is very scarce and limited to model solvents 26,27 .…”
Section: Introductionmentioning
confidence: 99%